Does a Unique Neuropsychiatric Profile Currently Exist for Chronic Traumatic Encephalopathy? - Hanlon, Faith M. (Curr Sports Med Rep, 2017)
There is evidence that repetitive mild traumatic brain injury leads to specific patterns of neuropathological findings, labeled chronic traumatic encephalopathy (CTE). However, questions remain about whether these neuropathological changes produce changes in behavior, cognition and emotional status that are associated with a unique neuropsychiatric profile that can be assessed using currently available clinical tools. Our review of the literature indicates that insufficient evidence currently exists to suggest a distinct neuropsychiatric profile for CTE. Major limitations to the field presently include the relatively nascent nature of the topic, reliance on retrospective next-of-kin reporting, the lack of prospective studies, and similarities in neuropsychiatric symptoms between CTE, other neurodegenerative disorders and forms of psychopathology. Clinicians and researchers alike have a responsibility to adopt a cautious and balanced approach for ante-mortem assessments to minimize the potential unintended negative consequences of both over- and under-diagnosing a clinical entity that has yet to be clearly established.